The School of Reading Osip Mandelshtam: Readers No. 1, 2, 3 - Timenchik, Roman (Literatūra, 2020)
“To prove now, that the history of literature is not only the history of writers, but also the history of readers […] means to belabor the obvious,” stated Alexander Beletskii a century ago, but the task of the detailed detecting of the separate groups, or rather to use Boris Tomashevskii’s term, “schools” of readers, is still vital for the historians of modern Russian poetry. The following is the attempt to name the first “enrollees” of the school of reading Osip Mandelshtam’s poetry, two of them sharing his activities in the literary workshop “The Guild of the Poets” in St. Petersburg in the 1910s, and the third being the poet’s wife during 1919–1938.
Keywords: Osip Mandelstam; Nikolai Gumilev; Anna Akhmatova; Nadezhda Mandelstam; schools of reading Russian poetry of the 20th century; titles-intertexts